Antibacterial acticivity of extracts from Potentilla reptans L. - Irena Mincheva; Maya M. Zaharieva; Daniela Batovska; Hristo Najdenski; Iliana Ionkova; Ekaterina Kozuharova (Pensoft Publishers, 2019)
Potentilla reptans is widely used in traditional medicine as an astringent, for treating diarrhoea, haemorrhoids and for bleeding gums. A recent ethnobotanical study has reported on the anti-mastitis effects of the aerial parts of P. reptans decoction. The aim of the present study is to evaluate the antibacterial potential of extracts and fractions, obtained from aerial parts of P. reptans against three strains of Staphylococcus aureus. The observed MICs were within the range of 0.325 - 2.5 mg/ml. Studied extracts and their fractions exerted mostly bacteriostatic effect, with the n-hexane fraction of hydroethanolic extract being the most active (MIC 0.313 mg/ml against S. aureus ATCC 6538 P). However, further investigations are necessary to reveal the precise mode of action of P. reptans against mastitis.